2020
DOI: 10.3389/fpsyg.2020.01303
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Psychological Well-Being: Revisiting the Role of Subjective Socioeconomic Status

Abstract: Socioeconomic status (SES) is a complex and multidimensional construct, encompassing both independent objective characteristics (e.g., income or education) and subjective people's ratings of their placement in the socioeconomic spectrum. Within the growing literature on subjective SES belongingness and psychological well-being, subjective indices of SES have tended to center on the use of pictorial rank-related social ladders where individuals place themselves relative to others by simultaneously considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
69
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 57 publications
13
69
2
8
Order By: Relevance
“…We documented that the household-income level of trustees outweighed the other status cues we manipulated in this study. Social status is a multidimensional phenomenon, and previous research has shown that not all of these dimensions affect personal dispositions similarly (Navarro-Carrillo et al, 2020;Trautmann et al, 2013). Nonetheless, the effect of income on trustworthiness has been documented (Ermisch & Gambetta, 2016), and in line with previous research indicating that the poor are more attuned to the economic dimensions of everyday experiences (Shah et al, 2018), it seems that household income is, for them, a more meaningful status cue in risky economic exchanges.…”
Section: Discussionsupporting
confidence: 57%
“…We documented that the household-income level of trustees outweighed the other status cues we manipulated in this study. Social status is a multidimensional phenomenon, and previous research has shown that not all of these dimensions affect personal dispositions similarly (Navarro-Carrillo et al, 2020;Trautmann et al, 2013). Nonetheless, the effect of income on trustworthiness has been documented (Ermisch & Gambetta, 2016), and in line with previous research indicating that the poor are more attuned to the economic dimensions of everyday experiences (Shah et al, 2018), it seems that household income is, for them, a more meaningful status cue in risky economic exchanges.…”
Section: Discussionsupporting
confidence: 57%
“…It is claimed that objective indicators ‘produce’ social status, and that people's perceived social status is health-enhancing ( Marmot, 2004 ). However, little is known about the relative importance of these indicators in the subjective assessment of individuals' placement in the social hierarchy ( Navarro-Carrillo et al, 2020 ). Furthermore, the literature has confirmed a lasting impact of childhood SEP on adult health and socioeconomic conditions ( Case et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we have quantified respondents' implicit weighting of education, occupation and income in explaining their own subjective SEP, as the relative importance of these factors is not well understood in the assessment of subjective SEP ( Navarro-Carrillo et al, 2020 ). We have further provided new insights into the importance of childhood SEP, measured using childhood financial circumstances and parents’ education level, in determining subjective SEP, to investigate whether there are determinants of adult subjective SEP that can be traced back to early-life conditions, independently of objective SEP.…”
Section: Introductionmentioning
confidence: 99%
“…The association between income and wellbeing is similar to the subjective SES pictorial or ladder scale and wellbeing correlation (r = .22) but stronger than the perceived SES and wellbeing association (Tan et al, 2020;Howell & Howell, 2008;Zell et al, 2018). Navarro-Carrillo et al (2020) revisited the role of subjective social class in the social class-psychological well-being relationship. They adapted the MacArthur Scale of Subjective Social Status (Adler et al, 2000)-a pictorial social ladder that represents one of the most widely used measures-to income, education, and occupation.…”
mentioning
confidence: 76%
“…
This monograph presents a set of studies that examine the psychosocial determinants of well-being. Navarro-Carrillo et al (2020) analyzes in this monograph a classic issue: the association between different measures of socioeconomic status (i.e., objective and subjective) and psychological well-being. Objective SES is usually measured by income and educational attainment.
…”
mentioning
confidence: 99%